How to change your mind : the new science of psychedelics - Pollan, Michael, 1955- ([London] : Allen Lane, an imprint of Penguin Books, 2018)
Een boek over het gebruik van geestesverruimende middelen, paddenstoelen en LSD in het bijzonder.
Keywords: Hallucinations and illusions -- Social aspects; Hallucinogenic drugs -- History; Hallucinogenic drugs -- Physiological effect; Hallucinogenic drugs -- Psychological aspects